Hubungan Usia Ibu Hamil dengan Kejadian Abortus Spontan di Rumah Sakit Umum Cut Meutia Kabupaten Aceh Utara Tahun 2020 - Sufia Rahma; Juwita Sahputri; Cut Sidrah Nadira (Publikasi Indonesia, 2022)
Spontaneous abortion is the end of a pregnancy with a gestational age of less than 20 weeks or weighing less than 500 grams that occurs naturally. The Indonesian Research and Development Agency stated that 4.1% of maternal deaths in Indonesia were caused by spontaneous abortion, where the target for reducing the MMR in 2021 is 0.22%. This incident was triggered by several factors including the age of the mother. Preliminary data survey at RSU Cut Meutia found that there was a fairly high increase in the incidence of spontaneous abortion in 2020 compared to 2019 (108%). This study aims to determine the relationship between maternal age and the incidence of spontaneous abortion at RSU Cut Meutia, North Aceh Regency in 2020. This study was an analytical observational study with a cross sectional approach, carried out from October 25 to November 3, 2021. The data in this study were all pregnant women who experienced spontaneous abortion in 2020, and obtained from secondary data as many as 71 people. The statistical test used was Kolmogorov-Smirnov. The results of univariate analysis showed that 55.6% of spontaneous abortions occurred in the age group of 20-35 years. It was also found that the highest type of abortion was incomplete abortion (68.3%). In bivariate analysis, p = 1,000. Therefore, it can be concluded that maternal age is not significantly associated with the incidence of spontaneous abortion.